Relationship of Geriatric Nutritional Risk Index (GNRI) with length of hospitalization and mortality rate in elderly patients - Neneng Ratnasari, Retno Ambarukminingsih I Dewa Putu Pramantara (Universitas Gadjah Mada, 2014)
The proportion of elderly population is growing faster than any other age group. Malnutrition isa widespread problem in elderly and has been recognized as the most common cause of mortalityand morbidity. Mini Nutritional Assessment (MNA) is recommended to detect malnutrition riskamong geriatrics. However, it is just appropriate for geriatric who stay at home. For hospitalizationpatients, Nutritional Risk Index (NRI) that using albumin and weight is recommended. However,the weight data is often not possible obtained in geriatrics. Therefore, Geriatric Nutritional RiskIndex (GNRI) using ideal body weight is recommended. The aim of this study was to evaluaterelationship of GNRI with length of hospitalization and mortality rate in geriatric patients. Thiswas an observational study with a prospective cohort design conducted in Dr. Sardjito GeneralHospital, Yogyakarta from January to February 2012. Patients who met the inclusion and exclusioncriteria were recruited. Laboratoty and clinical examinations as well as GNRI scoring were thenperformed. Patients were grouped into two groups i.e. patients with GNRI score < 82 and eâ82. The patients were then monitored during hospitalization until they were discharged due todie or recovered. The length of stay and patients died were then recorded. The results showedthat the length of stay of patients with GNRI score < 82 (14.32 Â± 8.20 days) was significantlylonger than those with GNRI score ï³82 (9.31 Â± 6.15 days) (p = 0.006). Moreover, the mortalityrate of patients with GNRI score < 82 (42.1%) was significantly higher than those with GNRIscore ï³82 (2.8%) (p = 0.000). Kaplan-Meier survival analysis showed survival rate of patientswith GNRI score <82 rapidly decreased when compared with those with GNRI score ï³82. Inconclusion, there is negative correlation between GNRI with length of hospitalization and mortalityrate in elderly.